Sarcopenic Obesity Is Significantly Associated With Coronary Artery Calcification - Chung, Goh Eun; Park, Hyo Eun; Lee, Heesun; Kim, Min Joo; Choi, Su-Yeon; Yim, Jeong Yoon; Yoon, Ji Won (Frontiers in Medicine, 2021)
Background: An association between sarcopenic obesity and cardiovascular disease has been suggested. We investigated the relationship between sarcopenia and coronary atherosclerosis, taking into account the presence or absence of obesity, in an apparently healthy population. Methods: Data were reviewed for subjects who underwent bioelectrical impedance analysis (BIA) and coronary calcium scoring (CAC) computed tomography between January 2017 and December 2018. Appendicular skeletal muscle mass (ASM) was assessed using BIA. Sarcopenia was defined as an ASM% (ASM/body weight) more than two standard deviations below the sex-specific mean for healthy young adults. CAC scores were dichotomized as low (<100) or high (≥100). Results: Among 1,282 subjects (mean age, 58.1 years; 75.5% male), the prevalence of high CAC was 21%. When the study population was divided into four groups according to their obesity and sarcopenia status, the prevalence of high CAC in the sarcopenic-obesity (SO) group was significantly higher than in the other groups (40.7%, P<0.001). After adjusting for age, sex, hypertension, diabetes, dyslipidemia, and creatinine, subjects with SO exhibited a significantly higher odds of a high CAC score, compared with the non-sarcopenic, non-obese group (odds ratio, 1.92; 95% confidence interval, 1.16–3.18, P=0.011). Conclusion: SO was significantly associated with CAC, independent of known risk factors for coronary artery disease. These findings suggest that sarcopenia and obesity may potentiate each other to increase atherosclerotic burden in coronary arteries, which may eventually lead to adverse cardiovascular events.